Production Process of Making Custom Part Rotary Housing on Milling Machines at PT. Anugrah Petrindo Moratama - Johannes Pietra Simamora; Oleh; Tee Boy Jhonson Simamora (Universitas Medan Area, 2026)
This internship was conducted at PT. Anugrah Petrindo Moratama, a company engaged in engineering and manufacturing. The purpose of this activity was to understand the production process of manufacturing a custom Rotary Housing part using lathe and milling machines. The methods applied included direct observation, primary data collection, and comparative analysis between theoretical knowledge and field practice. The main material used was Gray Cast Iron due to its suitable mechanical properties for Rotary Housing components. The production process consisted of client request handling, product design using software, raw material selection, engineering processes using lathe and milling machines, and quality control stages. The calculation results show that cutting speed and spindle rotation significantly affect production time; the higher the RPM, the shorter the machining duration. This internship provided practical experience for students to understand the real application of production process theory and broaden their knowledge of manufacturing industry operations.